Islamic banking and finance : an integrative approach - Zubair Hassan (Oxford Universiti Press, 2015)
The book aims to meet the needs of undergraduate students studying business and economics, though parts of it may be useful to guide students further along the learning curve. Apart from students, the book can also be used by professionals to refresh and update their knowledge and understanding on the subject, to help them carry out their responsibilities more efficiently. This book provides a comprehensive presentation of topics, including the theoretical foundations, financial instruments, banking operations, risk management, takaful, and issues relating to the law, regulation and governance. It integrates mainstream and Islamic perspectives to provide students with real-world financial structures